A review on wood downdraft gasifier plant design for Biomethane gas production - Kumar S.; Shukla S.K. (My University, 2025)
Gasification is a thermo-chemical process for converting a solid fuel into a mixture of combustible gases known as product gas. Product gas contains carbon monoxide, Hydrogen, carbon dioxide, methane, water vapor, nitrogen, tar (Heavy Hydrocarbons), sulphur compounds, and particulate matter etc. Although the potential of the process is high in terms of uses and expenditure but the problem is to eradicate the hazardous contents present in the form of residues. Emission has also become the main drawback in the uses of product gas. The quality of the product gas depends on design and operating parameters of the gasifier. The idea of gasifier design should be in such a way that it can convert the solid biomass like wood particulate, organic and inorganic wastes into the form clean product gas. Tar can be removed either through physical techniques or by catalytic cracking or by thermal cracking or combination of these. A suitable composition of the syngas has to be collected which will be useful for extracting bio-methane gas. This paper reviews extensively on techniques to obtain a clean product-gas and ways to extract Bio-methane to use it directly or as a supplement with diesel to run a diesel generator for electricity generation. © 2015 IEEE.